The Effect of Customer Service Performance and Accountability on Customer Satisfaction Perumda BPR Bank Regional Lamongan - Titin (Enrichment : Journal of Management, 2020)
In the world of banking, there is human resource management that is the spotlight and the foundation of a financial institution to survive. Human resources have a major role in an organizational activity and are the most important resources to win the competition. Especially in the era of the industrial revolution 4.0 like today, it requires a bank to be trustworthy and able to provide the best customer service performance so that it can be accepted by the public. This study aims to determine the partial effect of customer service performance, and accountability on customer satisfaction, to determine the simultaneous effect of customer service performance, and accountability partially influence customer satisfaction PERUMDA BPR Bank Daerah Lamongan, and the two variables (customer service performance and accountability. ) which one has the most dominant influence on customer satisfactionm PERUMDA BPR Bank Daerah Lamongan. This study uses quantitative methods, the population used is the customers of PERUMDA BPR Bank Daerah Lamongan. The number of samples in this study were 100 customers using analysis tools of validity test, reliability test, classical assumption test, multiple linear regression, multiple correlation, coefficient of determination, and hypothesis testing (t test and F test). From the analysis using SPSS 22 for Windows. From the results of the study it can be concluded that the variables of customer service performance and accountability partially influence customer satisfaction, customer service and accountability variables simultaneously influence customer satisfaction. And the variable that has the most dominant influence on customer satisfaction at PERUMDA BPR Bank Daerah Lamongan is accountability (X2)..